Creative Content of Madura Youtubers as A Source of Income In Review Of Islamic Business Ethics - Maulana, Moh.Imron; Fahrurrozi; Fadli, Royyan (International Journal of Islamic Business and Management Review, 2025)
This study aims to analyze the creative content management of Madura Youtubers, identify monetization mechanisms that are a source of income, and evaluate these practices based on Islamic business ethics principles. The research uses a descriptive qualitative approach with data collection techniques in the form of interviews, observations, and documentation of several Madura Youtubers who are active in producing digital content. The results of the study show that creative content management is carried out through the process of idea planning, theme development, audiovisual production, editing, and distribution strategies that highlight Madura's cultural identity. The source of income for Youtubers comes from AdSense, endorsements, sponsorships, and promotional cooperation with local MSME actors. However, this monetization mechanism also presents challenges, including reliance on YouTube's algorithm, revenue fluctuations, and the potential for ads that are not in line with sharia principles. An evaluation based on Islamic business ethics shows that most Madura Youtubers have applied the principles of honesty (ṣidq), justice ('adl), trust, and usefulness (maṣlaḥah), although there are still practices that need to be improved, such as the use of clickbait and less selective advertising settings. This study concludes that the creative and monetization practices of Madura Youtubers are basically in line with Islamic business ethics values, but require strengthening the aspects of transparency, content selectivity, and avoidance of syubhat elements. This finding is expected to be a reference for Muslim digital creators in developing content that is productive, economically valuable, and still in accordance with sharia principles.